On the Use of Articles in English and in Hungarian - Kovács Éva; Єва Ковач (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2023)
Abstract. The English article system presents many problems for non-native speakers of English, thusto Hungarian learners of English as well, and due to the influence of the mother tongue they commit many errors in using them. While the definite article is the most basic indicator of definiteness, the indefinite article is the most basic indicator of indefiniteness for singular count nouns. However, there is a third type of article, the zero article, which indicates that the noun phrase is used in a generic sense in English whereas in Hungarian the definite article is used here. (e.g., Milk is good for you. Cigarettes are bad for your health. Do you like folk music? vs. A tej jó neked. A cigaretta káros az egészségedre. Szereted a népzenét). Although there are many similarities in the use of articles in English and Hungarian, there are also many crucial differences in this respect between the two languages as illustrated by the examples above. The main aim of this paper is to investigate these similarities and differences by primarily relying on descriptive grammar books commonly used by students during their studies at universities. Special focus will be placed on the use of articles for generalisation (e.g., The bull terrier makes an excellent watchdog./A bull terrier makes an excellent watchdog./Bullterriers make excellent watchdogs. vs. A bullterrier kitűnő házőrző.) and with proper nouns (e.g., Westminster Abbey vs. A Westminster- apátság or Lake Balaton vs. A Balaton, Mont Blanc vs. A Mont Blanc), as these are the most troublesome areas students face when studying the article system of English. I hope to be able to improve students’ understanding of this difficult area and guide them to a more accurate usage of the English article system.

Резюме. У статті зазначено, що система англійських артиклів створює багато проблем для неносіїв англійської мови, а отже, і для угорців, які вивчають англійську мову.Через вплив рідної мови вони припускаються багатьох помилок у їх використанні. У той час як означений артикль є основним показником означеності, неозначений артикль – основним показником неозначеності для іменників в однині. Однак існує третій тип артикля – нульовий артикль, який вказує на те, що в англійській мові іменникове словосполучення вживається в загальному значенні, тоді як в угорській мові у такому випадку вживається визначений артикль. (наприклад, Milk is good for you. Cigarettes are bad for your health. Do you like folk music? vs. A tej jó neked. A cigarettа káros az egészségedre. Szereted a népzenét?). Зроблено висновок, що незважаючи на те, що вживання артиклів в англійській та угорській мовах має багато спільних рис, між двома мовами у цьому плані існує також багато суттєвих відмінностей, як показано в наведених вище прикладах. Основна мета цієї статті – дослідити ці подібності та відмінності, спираючись насамперед на підручники з описової граматики, якими зазвичай користуються студенти під час навчання в університетах. Особливу увагу приділено використанню артиклів для узагальнення (наприклад, The bull terrier makes an excellent watchdog./A bull terrier makes an excellent watchdog./Bullterriers make excellent watchdogs. vs. A bullterrier kitűnő házőrző.) та з власними іменниками (наприклад, Вестмінстерське абатство vs. A Westminster- apátság або Lake Balaton vs. A Balaton, Mont Blanc vs. A Mont Blanc), оскільки це найбільш проблемні моменти, з якими стикаються студенти при вивченні артиклевої системи англійської мови. Сподіваємося, що напрацювання цієї публікації зможуть покращити розуміння студентами цієї складної сфери та направити їх на більш точне використання системи англійського артикля.

Az angol névelő használata sok problémát okoz a nem anyanyelvi beszélőknek, így a magyar anyanyelvű tanulóknak is, akik az anyanyelv hatása miatt sok hibát követnek el a használatuk során. Míg a határozott névelő a határozottság legalapvetőbb jelzője, addig a határozatlan névelő a határozatlanság legalapvetőbb jelzője az egyes számú főnevek esetében. Létezik azonban egy harmadik típusú névelő, a nulla névelő, amely az angolban a főnévi igenév általános értelemben való használatát jelzi, míg a magyarban itt a határozott névelőt használjuk (például Milk is good for you. Cigarettes are bad for your health. Do you like folk music? Vs. A tej jó neked. A cigaretta káros az egészségedre. Szereted a népzenét). Bár az angol és a magyar nyelvben sok hasonlóság van a névelők használatában, a két nyelv között e tekintetben sok lényeges különbség is van, amint azt a fenti példák is mutatják. A tanulmány fő célja, hogy ezeket a hasonlóságokat és különbségeket vizsgálja, elsősorban a diákok által az egyetemi tanulmányaik során általánosan használt leíró nyelvtankönyvekre támaszkodva. Különös hangsúlyt fektetünk az általánosításra szolgáló névelők használatára (például The bull terrier makes an excellent watchdog./A bull terrier makes an excellent watchdog./Bullterriers make excellent watchdogs. vs. A bullterrier kitűnő házőrző.) and with proper nouns (e.g., Westminster Abbey vs. A Westminster- apátság or Lake Balaton vs. A Balaton, Mont Blanc vs. A Mont Blanc vs. A Mont Blanc) mivel ezek a legnehezebb területek, amelyekkel a diákok szembesülnek, amikor az angol nyelv névelőit próbálják elsajátítani. Az eredmények segíthetik a tanulókat a problémásabb nyelvtani szabályok begyakorlásában.
Про використання артиклів в англійській та угорській мовах
A névelők használatáról az angol és a magyar nyelvben
https://aab-philologica.kmf.uz.ua/aabp
Keywords: the definite article; the indefinite article; the zero article; common nouns; proper nouns; countability; generalisation